2022
DOI: 10.22438/jeb/43/2/mrn-1852
|View full text |Cite
|
Sign up to set email alerts
|

Crop performance, water use, economics and energy indices in rabi groundnut (Arachis hypogaea L.) under micro irrigation methods

Abstract: Aim: A field investigation was conducted during 2016-17 and 2017-18 to assess the relative performance of micro irrigation methods with regard to yield, water use, economics, nitrogen indices and energy use pattern in rabi groundnut on irrigated Alfisols. Methodology: One conventional and three micro-irrigation methods viz., drip, sprinkler and rain gun were evaluated in rabi groundnut. Besides growth, reproductive traits and pod yield, the information on nodule count, water use efficiency, economic benefits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Weedy check (control) recorded lowest net return (148669/ha). Our ndings were same like the results of Ramanjaneyulu et al (2022) who concluded that maximum net returns was obtained in the treatment were pre emergence herbicide and post emergence herbicide was applied. Our ndings are also accordingly to the ndings of (Mishra, 2020) and (Mavarkar et al 2015) who examined that net returns was minimum under untreated plot.…”
Section: Economicssupporting
confidence: 89%
“…Weedy check (control) recorded lowest net return (148669/ha). Our ndings were same like the results of Ramanjaneyulu et al (2022) who concluded that maximum net returns was obtained in the treatment were pre emergence herbicide and post emergence herbicide was applied. Our ndings are also accordingly to the ndings of (Mishra, 2020) and (Mavarkar et al 2015) who examined that net returns was minimum under untreated plot.…”
Section: Economicssupporting
confidence: 89%
“…Water plays a key role in plant growth and development, and the traditional irrigation method in China is large water irrigation, the monitoring of drought and irrigation or not depends on manual. This coarse mine irrigation method will not only waste water resources but also lead to soil salinization and loss of fertilizer [1][2]. The purpose of developing water-saving irrigation technology is to change people's traditional habit of watering the ground by irrigation, really start from the characteristics of crop water demand, and apply water directly to the soil near the plant roots to produce the maximum economic benefits of crops with the least amount of water [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-irrigation is widely used around the world on the basis of its high irrigation water utilization and low energy consumption, and it also improves crop quality and yields [1]. However, this economic and environmental potential can be put at risk by inadequate treatment of the water used.…”
Section: Introductionmentioning
confidence: 99%